Insights into phosphatase-activated chemical defense in a marine sponge holobiont. Issue 6 (12th October 2021) - Jomori, Takahiro; Matsuda, Kenichi; Egami, Yoko; Abe, Ikuro; Takai, Akira; Wakimoto, Toshiyuki
Abstract : The phosphatase that activates calyculin biogenesis in the sponge Discodermia calyx turned out to originate from the bacterial symbiont Entotheonella. Abstract : Marine sponges often contain potent cytotoxic compounds, which in turn evokes the principle question of how marine sponges avoid self-toxicity. In a marine sponge Discodermia calyx, the highly toxic calyculin A is detoxified by the phosphorylation, which is catalyzed by the phosphotransferase CalQ of a producer symbiont, " Candidatus Entotheonella" sp. Here we show the activating mechanism to dephosphorylate the stored phosphocalyculin A protoxin. The phosphatase specific to phosphocalyculin A is CalL, which is also encoded in the calyculin biosynthetic gene cluster. CalL represents a new clade and unprecedently coordinates the heteronuclear metals Cu and Zn. CalL is localized in the periplasmic space of the sponge symbiont, where it is ready for the on-demand production of calyculin A in response to sponge tissue disruption.